Quality of Life in University Students with Disabilities: Systematic Review / Calidad de vida en estudiantes universitarios con discapacidad: revisión sistemática - María Guadalupe Ureña Rodríguez; Cristina Jazmín González Flores; Rosa Martha Meda Lara (RICSH Revista Iberoamericana de las Ciencias Sociales y Humanísticas, 2018)
The purpose of this systematic review was to identify the studies carried out through time referring to the quality of life of university students with disabilities, instruments used to measure it, as well as the setting where those were applied.  The search was done through EBSCO, SAGE Journals, SCOPUS, and RedALyC databases, and studies from 1994 to 2016 were found.  Preferred Reporting Items for Systematic Review and Meta-analysis (PRISMA) and quality assessment were used in the 6 selected papers.  Studies reveal quality of life and higher education students with disabilities are a scarcely studied coupling which generates invisibility in academic terms.